2006
DOI: 10.1104/pp.106.085936
|View full text |Cite
|
Sign up to set email alerts
|

The Key Role of Chlorocatechol 1,2-Dioxygenase in Phytoremoval and Degradation of Catechol by Transgenic Arabidopsis

Abstract: Transgenic exploitation of bacterial degradative genes in plants has been considered a favorable strategy for degrading organic pollutants in the environment. The aromatic ring characteristic of these pollutants is mainly responsible for their recalcitrance to degradation. In this study, a Plesiomonas-derived chlorocatechol 1,2-dioxygenase (TfdC) gene (tfdC), capable of cleaving the aromatic ring, was introduced into Arabidopsis (Arabidopsis thaliana). Morphology and growth of transgenic plants are indistingui… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 25 publications
1
12
0
Order By: Relevance
“…Among the seven phenols tested, PtUGT72B1 from P. trichocarpa was confirmed to catalyze the O -glucosylation of phenol, hydroquinone, and catechol when expressed in A. thaliana and P. pastoris . Phenol, hydroquinone, and catechol [32] have significant toxicities to A. thaliana . Plants transform xenobiotics via a three-phase detoxification system: conversion, conjugation, and compartmentalization [33].…”
Section: Discussionmentioning
confidence: 99%
“…Among the seven phenols tested, PtUGT72B1 from P. trichocarpa was confirmed to catalyze the O -glucosylation of phenol, hydroquinone, and catechol when expressed in A. thaliana and P. pastoris . Phenol, hydroquinone, and catechol [32] have significant toxicities to A. thaliana . Plants transform xenobiotics via a three-phase detoxification system: conversion, conjugation, and compartmentalization [33].…”
Section: Discussionmentioning
confidence: 99%
“…Although the toxicity of 2,3‐dihydroxy‐chlorobiphenyls to plants has never been examined directly, Camara and colleagues () have shown they are toxic to bacterial cells, Novakova and colleagues () have shown they are toxic to tobacco plants and Lovecka and colleagues () have shown that monohydroxylated PCB metabolites are toxic to plants depending on number and position of the chlorine atoms. Furthermore, the toxicity of catechol to plants has been clearly demonstrated by Liao and colleagues (). These are among the many observations supporting the use of transgenic plants producing 2,3‐DHBD for rhizoremediation of PCB‐contaminated sites since these plants are likely to be more resistant to the PCB metabolites produced by plants and their associated rhizobacteria than the non‐transgenic parents.…”
Section: Exploiting Plants To Promote Pcb Degradation By Rhizosphere mentioning
confidence: 94%
“…Co-expression of HPS and PHI in tobacco plants resulted in 20% reduction of formaldehyde compared to the control plants (Chen et al, 2010 ). In another study, a chlorocatechol 1,2-dioxygenase gene ( tfdC ) derived from the bacteria Plesiomonas was introduced into Arabidopsis thaliana (Liao et al, 2006 ). Transgenic plants showed enhanced tolerances to catechol, an aromatic ring.…”
Section: Development Of Phylloremediation Technologiesmentioning
confidence: 99%